Strategi Pengembangan Bahan Ajar Agama Buddha Pada Siswa Sekolah Minggu Buddha Kabupaten Kotawaringin Barat Berbasis Media Pembelajaran Interaktif - Prita Puspita; Mettadewi Wong; Adriana Venny Ariani; Linawati Suwito; Mulyadi Mulyadi (Jurnal Budi Pekerti Agama Buddha, 2023)
This research aims to determine the extent of the quality of the teaching materials used and develop teaching materials that are adapted to the characteristics of learners, due to the limitations of the teaching materials that have been used and create new teaching materials that are more appropriate and appropriate for student education in West Kalimantan Province. This research method uses a qualitative approach with R&D research methods. The subjects in this research were 42 students in West Kalimantan Province. The research and development procedure for the R& model consists of five steps, namely; (1) Analysis (analysis), (2) Design (design), (3) Development (development), (4) Implementation (implementation) and (5) Evaluation (evaluation). The results of the analysis show that the Buddhist Vihara Graha Sailendra Sunday School learning conditions at this week's school are still teacher-centered using printed books and limited use of learning media. It was found from the results of post-test data from 42 students that only 39 reached the KKM on Buddhist religious holiday material, while 3 did not reach the KKM.